The effect of yeast on the treatment and prevention of experimentally induced cerebrocortical necrosis in lambs - Mahmut Ok; Kemal Irmak; Mustafa Ortatatlı; Veysi Aslan; Kemal Çiftçi; ismail Şen; Fatih M. Birdane (Eurasian Journal of Veterinary Sciences)
The effect of yeast on the treatment and prevention of the cerebrocortical necrosis (CCN) induced experimentally by amprolium in lambs was investigated in this study. Nine healthy lambs (aging between 6 and 8 months, and weighing between 14 and 16 kg) were used as a material. Nine lambs were divided into 3 groups. Each group had 3 animals. Amprolium (600 mg/kg/ day) was given to induce CCN orally to all the groups during experiment by stomach tube. Yeast (2 g/kg/day) was given orally to the lambs of group 1 and 3 to treat and to prevent the CCN. The lambs of all the groups exhibited clinical findings related with CCN between 24 and 62 days of the ex-periment, except two lambs of the group 1. Serum ALT and glucose concentrations increased (p <0.05, p<0.01), and plasma thiamine concentration decreased (p <0.05, p<0.01) in all of the lambs. Meningial hyperemia, swelling and oedematous brain were observed in alt of the lambs, excluding lambs 1 and 3 in the necropsy. Histologically, ischemic neuronal changes, perivascular and perineuronal oedema and focal necrosis were determined in cerebellar cortex in all of the lambs, excluding lambs 1 and 3. The results of this study showed that using of yeast might have beneficial in the prevention of the CCN in lambs.